Arterial Hypertension Aggravates Innate Immune Responses after Experimental Stroke - Möller, Karoline; Pösel, Claudia; Kranz, Alexander; Schulz, Isabell; Scheibe, Johanna; Didwischus, Nadine; Boltze, Johannes; Weise, Gesa; Wagner, Daniel-Christoph (Frontiers in Cellular Neuroscience, 2015)
Arterial hypertension is not only the leading risk factor for stroke, but also attributes to impaired recovery and poor outcome. The latter could be explained by hypertensive vascular remodeling that aggravates perfusion deficits and blood–brain barrier disruption. However, besides vascular changes, one could hypothesize that activation of the immune system due to pre-existing hypertension may negatively influence post-stroke inflammation and thus stroke outcome. To test this hypothesis, male adult spontaneously hypertensive rats (SHRs) and normotensive Wistar Kyoto rats (WKYs) were subjected to photothrombotic stroke. One and 3 days after stroke, infarct volume and functional deficits were evaluated by magnetic resonance imaging and behavioral tests. Expression levels of adhesion molecules and chemokines along with the post-stroke inflammatory response were analyzed by flow cytometry, quantitative real-time PCR and immunohistochemistry in rat brains 4 days after stroke. Although comparable at day 1, lesion volumes were significantly larger in SHR at day 3. The infarct volume showed a strong correlation with the amount of CD45 highly positive leukocytes present in the ischemic hemispheres. Functional deficits were comparable between SHR and WKY. Brain endothelial expression of intercellular adhesion molecule 1 (ICAM-1), vascular cell adhesion molecule 1 (VCAM-1), and P-selectin (CD62P) was neither increased by hypertension nor by stroke. However, in SHR, brain infiltrating myeloid leukocytes showed significantly higher surface expression of ICAM-1 which may augment leukocyte transmigration by leukocyte–leukocyte interactions. The expression of chemokines that primarily attract monocytes and granulocytes was significantly increased by stroke and, furthermore, by hypertension. Accordingly, ischemic hemispheres of SHR contain considerably higher numbers of monocytes, macrophages and granulocytes. Exacerbated brain inflammation in SHR may finally be responsible for larger infarct volumes. These findings provide an immunological explanation for the epidemiological observation that existing hypertension negatively affects stroke outcome and mortality.